Electrochemical scale removal cathode material and preparation method thereof
Patent Information
- Application Number
- CN202611301611.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-09
AI Technical Summary
传统电化学除垢阴极普遍存在结垢覆盖快、有效反应面积衰减迅速、电极寿命短的行业痛点,现有改进方案大多仅停留在表面结构优化或单一材料替换层面,无法从根本上解决“OH⁻生成-结垢沉积-自发脱落”三者的协同矛盾
[0029]电极表面的氧化膜及油脂会削弱镀层与基体间的结合力,使得镀层表面有缺陷产生;本发明首先通过对电极基体进行预处理除去电极基体表面的氧化膜、油脂及酸洗活化,以增强镀层与基体间的结合力。
Abstract
Description
Technical Field
[0001] This invention relates to the field of cathode material technology, specifically to an electrochemical descaling cathode material and its preparation method. Background Technology
[0002] Circulating cooling water systems are crucial industrial heat exchange units, accounting for over 70% of total industrial water consumption. As water evaporates and is lost from the system, calcium... 2+ and Mg 2+ Once saturation is reached, hardness ions crystallize and precipitate, forming scale deposits on the inner walls of circulating system pipes and the surfaces of heat exchangers. Scale buildup reduces the flow area in pipes and clogs heat exchangers, increasing system energy consumption and reducing heat exchange efficiency. Effectively controlling the hardness ion content in the circulating water system is crucial for ensuring its safe and stable operation. Currently, common solutions to scaling problems in industrial circulating cooling water include chemical methods, physical scale inhibition methods, and methods for removing scale-forming ions from the water. Each method has its advantages and disadvantages, and none can fundamentally and completely solve the scaling problem in cooling water systems.
[0003] Electrochemical descaling technology, as an environmentally friendly water treatment technology, has gained increasing attention in recent years due to its advantages such as removing scale and preventing corrosion at the source; no added chemicals, thus avoiding secondary pollution; and the strong oxidizing agents such as chlorine produced by the anodic reaction, which not only reduce ammonia nitrogen but also have bactericidal and algae-killing effects. Traditional electrochemical descaling cathodes generally suffer from industry pain points such as rapid scale formation, rapid decay of effective reaction area, and short electrode lifespan. Existing improvement solutions mostly focus on surface structure optimization or single material replacement, failing to fundamentally resolve the synergistic contradiction between "OH⁻ generation, scale deposition, and spontaneous shedding." This invention breaks away from the conventional "single-functional layer stacking" design approach. It constructs a Ni-Co-Mo-P metal array on a metal substrate and then grows a low-surface-energy fluorinated polyether ultrathin transition layer in situ on the array surface. This completely confines the OH⁻ generation reaction to the inner high-porosity metal framework region, allowing calcium and magnesium scale deposition to occur only in the outer smooth low-surface-energy region. This achieves complete spatial separation between alkalinity generation and scale deposition, effectively improving the descaling efficiency and service life of the cathode. Summary of the Invention
[0004] The purpose of this invention is to provide an electrochemical descaling cathode material and its preparation method to solve the problems existing in the prior art.
[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution:
[0006] A method for preparing an electrochemical descaling cathode material, the method comprising the following steps:
[0007] (1) Pretreatment of the electrode substrate to obtain a pretreated electrode;
[0008] (2) A metal array is formed on one side of the pretreated electrode by a plating process to obtain a pre-modified electrode;
[0009] a. Preparation of electroplating solution;
[0010] b. Apply plating to the pretreated electrode;
[0011] c. Electrochemical activation treatment;
[0012] (3) An electrochemical descaling cathode material is prepared by forming a low surface energy fluoropolymer layer on the pre-modified electrode by ultrasonic spraying.
[0013] a. Preparation of fluorinated spraying solution;
[0014] b. Ultrasonic spray.
[0015] As an optimization, the pretreatment of the electrode substrate in step (1) includes the removal of the oxide film on the surface of the electrode substrate, the removal of grease, and acid washing activation.
[0016] As an optimization, the method for removing the surface oxide film is as follows: the electrode substrate is polished sequentially with wet sandpaper with a particle size of 600, 800 and 1000, rinsed with deionized water 3 to 5 times and then dried.
[0017] As an optimization, the method for removing the grease is as follows: immerse the electrode substrate in acetone, sonicate for 30-60 minutes, wash with deionized water 3-5 times, and then dry.
[0018] As an optimization, the acid washing and activation method is as follows: immerse the electrode substrate in a 5% to 10% hydrochloric acid aqueous solution for 10 to 30 seconds, then remove it, rinse it with deionized water 5 to 7 times, and then dry it.
[0019] As an optimization, the electrode substrate is a 304 stainless steel plate.
[0020] As an optimization, the preparation method of the electroplating solution in step (2) is as follows: nickel sulfate hexahydrate, trisodium citrate dihydrate, cobalt chloride, sodium acetate, sodium molybdate dihydrate, sodium hypophosphite monohydrate and potassium iodide are dissolved in deionized water in sequence, and the pH is adjusted to 9.5~10.0 using 0.1 mol / L sodium hydroxide aqueous solution to obtain the electroplating solution.
[0021] As an optimization, the concentration of nickel sulfate hexahydrate in the electroplating solution is 80 g / L, the concentration of trisodium citrate dihydrate is 30 g / L, the concentration of cobalt chloride is 12 g / L, the concentration of sodium acetate is 25 g / L, the concentration of sodium molybdate dihydrate is 15 g / L, the concentration of sodium hypophosphite monohydrate is 30 g / L, and the concentration of potassium iodide is 0.005 g / L.
[0022] As an optimization, the plating process for the pretreated electrode in step (2) is as follows: the electroplating solution is heated to 87°C, the pretreated electrode is placed in the electroplating solution, and the plating temperature is 0.03 A / cm. 2 Plating was performed at a current density for 60 minutes.
[0023] As an optimization, the electrochemical activation process in step (2) is as follows: the electroplated electrode is placed in a 1 mol / L KOH electrolyte, and a forward current of 35 mA is applied for 300 s, followed by a reverse current of -35 mA for 300 s, to complete 18 cycles of activation treatment. After rinsing with deionized water 3 to 5 times, the electrode is dried to obtain the pre-modified electrode.
[0024] As an optimization, the preparation method of the fluorinated spraying liquid in step (3) is as follows: dissolve perfluoropolyether diol and isophorone diisocyanate in ethyl acetate at a molar ratio of 1:1, add dibutyltin dilaurate at a mass of 0.003 to 0.005 times that of isophorone diisocyanate, and mix evenly to obtain a fluorinated spraying liquid with a solid content of 1 to 1.5 wt%.
[0025] As an optimization, the ultrasonic spraying process in step (3) is as follows: the fluorine-containing spraying liquid is sprayed onto the pre-modified electrode using an ultrasonic spraying device, the atomization flow rate is controlled at 6 mL / min, the spraying air pressure is 0.04 MPa, the substrate is heated to 75°C throughout the process, and after the spraying is completed, the electrode is placed in a 100°C oven for heat preservation and curing for 2 hours, and the film thickness is controlled at 20~25 μm to obtain the electrochemical descaling cathode material.
[0026] As an optimization, the molecular weight of the perfluoropolyether diol is 1000-5000.
[0027] The present invention also provides an electrochemical descaling cathode material prepared by the above-mentioned method.
[0028] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0029] The oxide film and grease on the electrode surface can weaken the bonding force between the coating and the substrate, resulting in defects on the coating surface. The present invention first removes the oxide film and grease on the electrode substrate surface by pretreatment and acid pickling activation, so as to enhance the bonding force between the coating and the substrate.
[0030] An electroplating solution was prepared by dissolving nickel sulfate hexahydrate, trisodium citrate dihydrate, cobalt chloride, sodium acetate, sodium molybdate dihydrate, sodium hypophosphite monohydrate, and potassium iodide in deionized water. A Ni-Co-Mo-P metal array was formed on one side of the pretreated electrode substrate through a plating process. The doping of molybdenum and phosphorus elements can regulate the electronic structure of the nickel-cobalt alloy, reduce the overpotential of the hydrogen evolution reaction, and shift the onset potential of the OH⁻ generation reaction towards a lower voltage direction, thus reducing the overall energy consumption of electrochemical descaling. The nickel-cobalt-molybdenum-phosphorus alloy itself exhibits far superior corrosion resistance under strongly alkaline circulating water conditions compared to a pure nickel layer, preventing pitting corrosion and passivation deactivation of the stainless steel substrate in a long-term high-alkaline environment, and extending the overall service life of the cathode.
[0031] A fluorinated reaction solution composed of perfluoropolyether diol and isophorone diisocyanate is sprayed onto the electrode. The perfluoropolyether diol and isophorone diisocyanate undergo a polymerization reaction on the electrode to generate a low surface energy fluorinated polymer coating in situ. This significantly reduces the adhesion between the scale layer and the electrode surface, completely confining the OH⁻ generation reaction to the inner high-porosity metal framework region. This allows calcium and magnesium scale deposits to form only in the outer smooth low surface energy region, achieving complete separation of alkalinity generation and scale deposition space. At the same time, it prevents scale from embedding inside the electrode and clogging the pores. Detailed Implementation
[0032] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0033] In the following specific implementation,
[0034] The electrode substrate is a 304 stainless steel plate with dimensions of 20×40 mm. 2 ;
[0035] The molecular weight of the perfluoropolyether diol is 2000;
[0036] The dimensionally stable anode mesh is a DSA anode with a specification of 20×60 mm. 2 .
[0037] Example 1:
[0038] A method for preparing an electrochemical descaling cathode material, the method comprising the following preparation steps:
[0039] (1) Pretreatment of the electrode substrate to obtain a pretreated electrode:
[0040] The electrode substrate was polished with wet sandpaper with grits of 600, 800 and 1000 in sequence, rinsed with deionized water 5 times and then dried.
[0041] The electrode substrate was immersed in acetone, sonicated for 40 minutes, rinsed with deionized water 5 times and dried.
[0042] The electrode substrate was immersed in a 10% hydrochloric acid aqueous solution for 10 seconds to activate it, then removed, rinsed with deionized water 5 times, and dried to obtain a pretreated electrode.
[0043] (2) A metal array is formed on one side of the pretreated electrode by a plating process to obtain a pre-modified electrode:
[0044] a. Preparation of electroplating solution:
[0045] Nickel sulfate hexahydrate, trisodium citrate dihydrate, cobalt chloride, sodium acetate, sodium molybdate dihydrate, sodium hypophosphite monohydrate, and potassium iodide were sequentially dissolved in deionized water. The pH was adjusted to 9.5 using a 0.1 mol / L sodium hydroxide aqueous solution to obtain the electroplating solution. The concentration of nickel sulfate hexahydrate was 80 g / L, the concentration of trisodium citrate dihydrate was 30 g / L, the concentration of cobalt chloride was 12 g / L, the concentration of sodium acetate was 25 g / L, the concentration of sodium molybdate dihydrate was 15 g / L, the concentration of sodium hypophosphite monohydrate was 30 g / L, and the concentration of potassium iodide was 0.005 g / L.
[0046] b. Plate the pretreated electrode substrate:
[0047] The electroplating solution was heated to 87°C, and the pretreated electrode was placed in the solution at 0.03 A / cm. 2 Plating was performed at a current density for 60 minutes;
[0048] c. Electrochemical activation treatment:
[0049] The electroplated electrode was placed in a 1 mol / L KOH electrolyte and energized with a 35 mA forward current for 300 s, then switched to a -35 mA reverse current for 300 s, completing 18 cycles of activation treatment. After rinsing with deionized water 5 times, the electrode was dried to obtain the pre-modified electrode.
[0050] (3) An electrochemical descaling cathode material is prepared by forming a low surface energy fluoropolymer layer on the pre-modified electrode using an ultrasonic spray method:
[0051] a. Preparation of fluorinated spraying solution:
[0052] Perfluoropolyether diol and isophorone diisocyanate were dissolved in ethyl acetate at a molar ratio of 1:1. Dibutyltin dilaurate was added at a mass ratio of 0.003 times that of isophorone diisocyanate. The mixture was then thoroughly mixed to obtain a fluorinated spraying liquid with a solid content of 1 wt%.
[0053] b. Ultrasonic spray:
[0054] Fluorine-containing spray liquid was sprayed onto the pre-modified electrode using an ultrasonic spraying device. The atomization flow rate was controlled at 6 mL / min and the spraying pressure was 0.04 MPa. The substrate was heated to 75°C throughout the process. After spraying, the electrode was placed in a 100°C oven for 2 hours to cure. The film thickness was controlled at 20 μm to obtain an electrochemical descaling cathode material.
[0055] Comparative Example 1:
[0056] The difference between the preparation method of the electrochemical descaling cathode material in Comparative Example 1 and Example 1 is that "sodium molybdate dihydrate" is not added during the preparation of the electroplating solution in step (2).
[0057] Comparative Example 2
[0058] The difference between the preparation method of the electrochemical descaling cathode material in Comparative Example 2 and Example 1 is that "sodium hypophosphite monohydrate" is not added during the preparation of the electroplating solution in step (2).
[0059] Comparative Example 3
[0060] The difference between the preparation method of the electrochemical descaling cathode material in Comparative Example 3 and Example 1 is that step (3) is not performed, and the "pre-modified electrode" obtained in step (2) is used as the "electrochemical descaling cathode material".
[0061] Comparative Example 4
[0062] The difference between the preparation method of the electrochemical descaling cathode material in Comparative Example 4 and Example 1 is that steps (2) and (3) are not performed; the "pre-treatment electrode" obtained in step (1) is used as the "electrochemical descaling cathode material".
[0063] Electrochemical testing:
[0064] A three-electrode system was used for measurements, with the saturated calomel potential as the reference electrode, the platinum electrode as the counter electrode, and the test sample electrode as the working electrode. Cathodic polarization spectroscopy (LSV) was performed on the examples and comparative examples at 25 °C to determine their hydrogen evolution overpotential. The test solution was 0.2 mol / L phosphate buffer (pH=8.2), and the scan range was E... ocp 0~E SCE -1.4 V, scan rate of 1 mV s -1 The results are shown in Table 1.
[0065] Table 1 - Current density at 10 mA / cm² 2 hydrogen evolution overpotential at time
[0066] hydrogen evolution overpotential hydrogen evolution overpotential Example 1 510mV Comparative Example 1 619mV Comparative Example 2 781mV Comparative Example 3 496mV Comparative Example 4 960mV
[0067] As shown in Table 1, the unplated stainless steel exhibits the highest hydrogen evolution overpotential and the worst hydrogen evolution performance. Doping with molybdenum and phosphorus can modulate the electronic structure of the nickel-cobalt alloy, reducing the overpotential of the hydrogen evolution reaction and decreasing the overall energy consumption of electrochemical descaling. Forming a low-surface-energy fluoropolymer layer on the electrode slightly increases the hydrogen evolution overpotential, but this increase is generally controllable. The slight increase is due to the fact that fluorinated polyethers are low-surface-energy insulating polymers, forming an ultra-thin covering layer on the surface of the nickel-cobalt-molybdenum-phosphorus active sites, partially blocking the direct electrocatalytic reaction sites and increasing the resistance to electron transport from the metal substrate to the electrolyte interface. The control is due to the fact that the ultrathin fluorinated polyether layer prepared by ultrasonic spray in-situ polymerization is not a completely dense and non-porous closed membrane. It retains a large number of microscopic ion diffusion channels, and water molecules and ions in the electrolyte can still easily penetrate to the inner nickel-cobalt-molybdenum-phosphorus active surface. It will not completely block the hydrogen evolution reaction. Although the hydrogen evolution overpotential increases slightly, the low surface energy effect brought by the fluorinated polyether layer allows the tiny bubbles generated by hydrogen evolution to quickly desorb from the electrode surface, avoiding the formation of an insulating gas film by the bubbles adhering to the electrode surface for a long time. On the contrary, it can avoid large fluctuations in the actual working overpotential of the electrode during long-term continuous operation.
[0068] Descaling rate and descaling speed test
[0069] A dimensionally stable anode mesh was selected as the anode in the electrochemical descaling process. During the electrochemical descaling process, the working area of both the cathode and anode immersed in the solution was the same, 20 × 40 mm. 2 A DC regulated power supply was used as the power source for the electrochemical descaling process. The electrolytic cell contained 3 L of electrolyte, and a submersible pump was used to circulate the water during the descaling process to ensure uniform mass transfer. The electrochemical descaling operating parameters were: electrolysis temperature 40℃, current density 50 A / m³. 2 The distance between the anode and cathode is 6 mm.
[0070] The composition of the scale-forming simulation solution is shown in Table 2;
[0071] Table 2
[0072] category Calcium chloride Sodium bicarbonate Sodium chloride content 0.777g / L 0.588g / L 0.225g / L
[0073] The water quality indicators of the scale-forming simulation solution are shown in Table 3;
[0074] Table 3
[0075] category Total hardness of water Total alkalinity electrical conductivity pH value numerical values 700mg / L 350mg / L 2500μS / cm 8.2±0.1
[0076] The cathode after electrochemical descaling was cleaned using a high-pressure cleaner. The high-pressure nozzle was fixed to an iron frame with clamps, and the distance between the nozzle and the cathode to be cleaned was fixed at 5 cm. The rinsing water was pressurized by a compressor and sprayed from the high-pressure nozzle in a 65° fan shape. The nozzle orifice diameter was 0.79 mm. The cathode was rinsed at water pressures of 3 MPa, 4 MPa, and 5 MPa, with each side rinsed for 10 seconds. After rinsing, the cathode was dried, weighed, and the scale removal rate was calculated.
[0077] The scale removal rate after the cathode is flushed with high-pressure water is calculated using the following formula:
[0078] ;
[0079] In the formula, M1 is the total mass of scale, M2 is the total mass of cathode and surface scale after high-pressure water rinsing and drying, and M3 is the mass of the cathode before electrochemical descaling; where M1 is calculated according to the following formula:
[0080] ;
[0081] In the formula, The hardness value is the simulated scale-forming solution before electrochemical descaling. V represents the hardness value of the simulated scale-forming solution after electrochemical descaling, and V represents the volume of the simulated scale-forming solution treated.
[0082] The average descaling rate of the cathode throughout the entire electrochemical descaling cycle is calculated using the following formula:
[0083] ;
[0084] In the formula, S is the working area of the cathode, and t is the electrochemical descaling time.
[0085] The test results are shown in Table 4.
[0086] Table 4
[0087] Scale removal rate (%) <![CDATA[Descaling rate (g / m 2 h)]]> Scale removal rate (%) <![CDATA[Scale removal rate (g / m 2 h)]]> Example 1 96.48 28.85 Comparative Example 1 85.67 18.71 Comparative Example 2 90.36 23.43 Comparative Example 3 92.98 25.58 Comparative Example 4 51.14 11.39
[0088] As shown in Table 4, the stainless steel without plating has the worst descaling performance. Forming a Ni-Co-Mo-P metal array on one side of the pretreated electrode through plating and forming a low surface energy fluoropolymer layer on the pre-modified electrode through ultrasonic spraying can significantly improve the descaling efficiency.
[0089] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing an electrochemical descaling cathode material, characterized in that, The preparation method of the electrochemical descaling cathode material includes the following steps: (1) Pretreatment of the electrode substrate to obtain a pretreated electrode; (2) A metal array is formed on one side of the pretreated electrode by a plating process to obtain a pre-modified electrode; a. Preparation of electroplating solution; b. Apply plating to the pretreated electrode; c. Electrochemical activation treatment; (3) An electrochemical descaling cathode material is prepared by forming a low surface energy fluoropolymer layer on a pre-modified electrode using an ultrasonic spraying method. a. Preparation of fluorinated spraying solution; b. Ultrasonic spray.
2. The method for preparing the electrochemical descaling cathode material according to claim 1, characterized in that, The pretreatment of the electrode substrate in step (1) includes the removal of the oxide film on the surface of the electrode substrate, the removal of grease, and acid washing activation; The method for removing the surface oxide film is as follows: the electrode substrate is polished sequentially with wet sandpaper with a particle size of 600, 800 and 1000, rinsed with deionized water 3 to 5 times and then dried. The method for removing the grease is as follows: immerse the electrode substrate in acetone, sonicate for 30-60 minutes, then wash with deionized water 3-5 times and dry. The acid washing and activation method is as follows: immerse the electrode substrate in a 5% to 10% hydrochloric acid aqueous solution for 10 to 30 seconds, then remove it, rinse it with deionized water 5 to 7 times, and then dry it.
3. The method for preparing the electrochemical descaling cathode material according to claim 2, characterized in that, The electrode substrate is a 304 stainless steel plate.
4. The method for preparing the electrochemical descaling cathode material according to claim 1, characterized in that, The preparation method of the electroplating solution in step (2) is as follows: nickel sulfate hexahydrate, trisodium citrate dihydrate, cobalt chloride, sodium acetate, sodium molybdate dihydrate, sodium hypophosphite monohydrate and potassium iodide are dissolved in deionized water in sequence, and the pH is adjusted to 9.5~10.0 using 0.1 mol / L sodium hydroxide aqueous solution to obtain the electroplating solution.
5. The method for preparing the electrochemical descaling cathode material according to claim 4, characterized in that, The electroplating solution contains nickel sulfate hexahydrate at a concentration of 80 g / L, trisodium citrate dihydrate at a concentration of 30 g / L, cobalt chloride at a concentration of 12 g / L, sodium acetate at a concentration of 25 g / L, sodium molybdate dihydrate at a concentration of 15 g / L, sodium hypophosphite monohydrate at a concentration of 30 g / L, and potassium iodide at a concentration of 0.005 g / L.
6. The method for preparing the electrochemical descaling cathode material according to claim 1, characterized in that, The process of plating the pretreated electrode in step (2) is as follows: heat the electroplating solution to 87°C, place the pretreated electrode in the electroplating solution, and plate it at 0.03 A / cm. 2 Plating was performed at a current density for 60 minutes.
7. The method for preparing the electrochemical descaling cathode material according to claim 1, characterized in that, The electrochemical activation process in step (2) is as follows: the electroplated electrode is placed in a 1 mol / L KOH electrolyte, and a forward current of 35 mA is applied for 300 s, followed by a reverse current of -35 mA for 300 s. This process is repeated for 18 cycles of activation. The electrode is then rinsed with deionized water 3 to 5 times and dried to obtain the pre-modified electrode.
8. The method for preparing the electrochemical descaling cathode material according to claim 1, characterized in that, The preparation method of the fluorinated spraying liquid in step (3) is as follows: dissolve perfluoropolyether diol and isophorone diisocyanate in ethyl acetate at a molar ratio of 1:1, add dibutyltin dilaurate at a mass of 0.003 to 0.005 times that of isophorone diisocyanate, and mix evenly to obtain a fluorinated spraying liquid with a solid content of 1 to 1.5 wt%.
9. The method for preparing the electrochemical descaling cathode material according to claim 1, characterized in that, The ultrasonic spraying process in step (3) is as follows: using an ultrasonic spraying device to spray the fluorine-containing spraying liquid onto the pre-modified electrode, controlling the atomization flow rate to 6 mL / min, the spraying air pressure to 0.04 MPa, heating the substrate to 75°C throughout the process, and placing the electrode in a 100°C oven for 2 hours after spraying to cure it. The film thickness is controlled at 20~25 μm to obtain the electrochemical descaling cathode material.
10. An electrochemical descaling cathode material prepared by the method according to any one of claims 1 to 9.